Changes in disease burden and epidemiological transitions - Gulis, Gabriel; Zidkova, Radka; Meier, Zdenek (Scientific reports, 2025)
The epidemiological transition has been characterized by demographic, societal and health changes in societies. Presuming that acute diseases, mostly of communicable etiology, are more important in terms of early-life mortality, whereas chronic diseases are responsible for a greater burden of disease throughout the life course, we attempt to develop an index to measure the stage of the epidemiological transition. Using Global Burden of Diseases, Risk Factors and Injuries (GBD) data available at https://vizhub.healthdata.org/gbd-compare/ on 04/04/2024 to calculate the Epidemiologic Transition Estimate (ETE) index as a ratio of YLD/YLL for the time period of 1990-2019. The values of the index ranged from 0.131 to 1.067 and 0.180 to 2.108 for males and females, respectively, across the 195 included countries. The transition process seems to be faster to females compared to males. The index shows consistently increasing values for five SDI-based country groups, with clear differences among the groups. Although more research and validation studies are needed despite all the uncertainties, the index seems to be robust to assess the progress in epidemiological transition. These findings can help to predict future social care and health system needs to address causes leading to YLD or YLL.
Keywords: dospělí; Female; Infant; dítě; předškolní dítě; novorozenec; Adult; mladý dospělý; ženské pohlaví; Epidemiologic transition; Adolescent; Global Health; celosvětové zdraví; globální zátěž nemocemi; lidé; Cost of Illness; Infant, Newborn; Global Burden of Disease; Burden of disease; Risk Factors; Global health; Male; kojenec; Aged; Child, Preschool; Young Adult; rizikové faktory; chronická nemoc; lidé středního věku; Child; senioři; mužské pohlaví; Chronic Disease; Middle Aged; mladiství; osobní újma zaviněná nemocí; Humans